2013
DOI: 10.1152/jn.00021.2013
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development of synaptic properties of the GABAergic projection from the inferior colliculus to the auditory thalamus

Abstract: Venkataraman Y, Bartlett EL. Postnatal development of synaptic properties of the GABAergic projection from the inferior colliculus to the auditory thalamus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 99 publications
3
33
0
Order By: Relevance
“…A recent study (Venkataraman and Bartlett, 2013) showed that electrical stimulation of the brachium of the IC elicited purely inhibitory response in 41% of medial geniculate neurons at postnatal day 27. It is possible that such neurons are driven exclusively by excitatory inputs from the cerebral cortex, and the ascending sensory information from the LG neurons modulates the corticothalamic input.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study (Venkataraman and Bartlett, 2013) showed that electrical stimulation of the brachium of the IC elicited purely inhibitory response in 41% of medial geniculate neurons at postnatal day 27. It is possible that such neurons are driven exclusively by excitatory inputs from the cerebral cortex, and the ascending sensory information from the LG neurons modulates the corticothalamic input.…”
Section: Discussionmentioning
confidence: 99%
“…Offset neurons are found in the IC and other auditory nuclei and depend on a balance of excitatory and inhibitory neurotransmission (Kasai et al, 2012). In developing rats, agerelated changes occur in the properties of IC inhibition and in GABAergic projections to the medial geniculate body (MGB) of the thalamus (Venkataraman and Bartlett, 2013b). The time course of these changes is similar to that of the development of temporal coding, as assessed by evoked potentials, in developing young rats (Venkataraman and Bartlett, 2013a).…”
Section: B Temporal Codingmentioning
confidence: 99%
“…This increase in myelination likely results in reductions in neural conduction time as measured by inter-wave peak latencies in the auditory brainstem response (ABR) (Salamy, 1984;Gorga et al, 1989;Moore et al, 1996;Hurley et al, 2005). Reductions in neural conduction time may also be attributed to changes in synaptic function-animal models have demonstrated rapid developmental changes in brainstem and midbrain synaptic function in infancy (Sanes, 1993;Venkataraman and Bartlett, 2013b). Developmental changes in phase locking properties of neurons may affect encoding of the frequency components of the acoustic signal.…”
Section: Introductionmentioning
confidence: 99%
“…The earlier development of low-frequency phase locking has also been demonstrated in midbrain structures (Pierson & Snyder-Keller, 1994;Romand & Ehret, 1990). Changes in synaptic transmission and increases in myelination may account for improved temporal precision with development (Brenowitz & Trussell, 2001;Sanes, 1993;Venkataraman & Bartlett, 2013).…”
mentioning
confidence: 89%
“…The group differences during the transition region may be associated with the development of synaptic efficiency during infancy. Venkataraman and Bartlett (2013) investigated GABAergic connections from the inferior colliculus to the thalamus in rat brain slices from three age groups (prehearing, immediate posthearing, and juvenile) and found that GABA inhibitory postsynaptic potentials Figure 5. Left panels: Average phase locking from individual responses to the /ga/ temporal fine structure (TFS) is represented in the timefrequency domain, with darker red colors indicating higher phase-locking frequency (PLF).…”
Section: Phase Lockingmentioning
confidence: 99%